2018
DOI: 10.3389/fphys.2018.01194
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Cycling Impairment in Heart Failure Is Exacerbated by Fibrosis: Insights Gained From Mechanistic Simulations

Abstract: Heart failure (HF) is characterized by altered Ca2+ cycling, resulting in cardiac contractile dysfunction. Failing myocytes undergo electrophysiological remodeling, which is known to be the main cause of abnormal Ca2+ homeostasis. However, structural remodeling, specifically proliferating fibroblasts coupled to myocytes in the failing heart, could also contribute to Ca2+ cycling impairment. The goal of the present study was to systematically analyze the mechanisms by which myocyte–fibroblast coupling could aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
2
14
0
1
Order By: Relevance
“…We assessed the effect of the fibrosis configurations on the APD and conduction velocity. Our results suggest that the presence of fibrosis produces a slight APD reduction, in agreement with Trenor et al [80] and Morgan et al [81]. A significant reduction in the conduction velocity was observed in all fibrosis configuration, with a larger effect observed at high fibrosis density.…”
Section: Discussionsupporting
confidence: 92%
“…We assessed the effect of the fibrosis configurations on the APD and conduction velocity. Our results suggest that the presence of fibrosis produces a slight APD reduction, in agreement with Trenor et al [80] and Morgan et al [81]. A significant reduction in the conduction velocity was observed in all fibrosis configuration, with a larger effect observed at high fibrosis density.…”
Section: Discussionsupporting
confidence: 92%
“…This association between OPTM of SERCA2 and myocardial fibrosis is consistent with the results of a previous study showing that myocardial fibrosis was mitigated by upregulation of SERCA2 in mice [33]. Further, a recent study reported that fibroblasts exacerbate [Ca 2+ ] c dysregulation in failing myocytes by reducing SR Ca 2+ content [34]. Thus, [Ca 2+ ] c dysregulation by fibroblast-myocyte coupling might further aggravate [Ca 2+ ] c dysregulation by OPTM of SERCA2.…”
Section: Discussionsupporting
confidence: 91%
“…hCICs were permitted to be coupled to cardiomyocytes or other hCICs; hMSCs were permitted to be coupled to cardiomyocytes or other hMSCs); G gap,k is the gap junctional conductance between a given cell and its k th neighbor; and V k is the membrane voltage of the k th neighbor. Adapted from Mora et al (2018), for the FHF-hCM model, 5 CFs were coupled to one HF-hCM with a gap junctional conductance of 1 nS. When incorporating the hMSC paracrine signaling variable and its anti-fibrotic effects (see section "Modeling Paracrine Signaling Effects" below for details), the corrected number of coupled CFs was rounded to the nearest integer.…”
Section: Simulating Heterocellular Coupling Between Cardiomyocytes and Non-excitable Cellsmentioning
confidence: 99%
“…To identify non-excitable cell ion channels responsible for influencing the action potential waveform, calcium transient, and net ionic channel charge of coupled HF-hCMs, we examined the model parameter sensitivity using an established multivariable regression analysis (Mayourian et al, 2016(Mayourian et al, , 2017Mora et al, 2018). More specifically, the prescribed hCIC, hMSC, and CF ion channel parameters of interest were randomly varied for 300 trials by a normally distributed pseudorandom scale factor with a coefficient of variation of 20%.…”
Section: Parameter Sensitivity Analysismentioning
confidence: 99%